Hearing Loss in Offspring Exposed to Antiretrovirals During Pregnancy and Breastfeeding - DeBacker, J. Riley; Langenek, Breanna; Bielefeld, Eric C. (Frontiers in Molecular Neuroscience, 2022)
Over 27 million people worldwide currently receive daily antiretroviral therapy for the management of HIV/AIDS. In order to prevent the continued spread of HIV, the World Health Organization (WHO) recommends the use of highly active antiretroviral therapy by pregnant and nursing women. There is currently little research into the auditory effects of this therapy on children exposed during pregnancy and breastfeeding, and research to date on the direct effects of antiretroviral exposure on the auditory system is inconclusive. The current study examined the effects of WHO-recommended first-line antiretrovirals in a well-controlled animal model to evaluate the potential for auditory damage and dysfunction following these exposures. Female breeding mice were each exposed to one of four antiretroviral cocktails or a vehicle control once daily during pregnancy and breastfeeding. Offspring of these mice had their auditory status evaluated after weaning using auditory brainstem responses and distortion-product otoacoustic emissions (DPOAEs). Auditory brainstem response thresholds following antiretroviral exposure during gestation and breastfeeding showed elevated thresholds and increased wave latencies in offspring of exposed mice when compared to unexposed controls, but no corresponding decrease in DPOAE amplitude. These differences in threshold were small and so may explain the lack of identified hearing loss in antiretroviral-exposed children during hearing screenings at birth. Minimal degrees of hearing impairment in children have been correlated with decreased academic performance and impaired auditory processing, and so these findings, if also seen in human children, suggest significant implications for children exposed to antiretrovirals during development despite passing hearing screenings at birth.